ln(1+x)-x=.1

Simple and best practice solution for ln(1+x)-x=.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(1+x)-x=.1 equation:


Simplifying
ln(1 + x) + -1x = 0.1
(1 * ln + x * ln) + -1x = 0.1
(1ln + lnx) + -1x = 0.1

Solving
1ln + lnx + -1x = 0.1

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add 'x' to each side of the equation.
1ln + lnx + -1x + x = 0.1 + x

Combine like terms: -1x + x = 0
1ln + lnx + 0 = 0.1 + x
1ln + lnx = 0.1 + x

Reorder the terms:
-0.1 + 1ln + lnx + -1x = 0.1 + x + -0.1 + -1x

Reorder the terms:
-0.1 + 1ln + lnx + -1x = 0.1 + -0.1 + x + -1x

Combine like terms: 0.1 + -0.1 = 0.0
-0.1 + 1ln + lnx + -1x = 0.0 + x + -1x
-0.1 + 1ln + lnx + -1x = x + -1x

Combine like terms: x + -1x = 0
-0.1 + 1ln + lnx + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| a+9=-50 | | ln(1+x)-x=0 | | (11x^4-2x)+(7x^4+12x-8)= | | -2w^2+7w-72=0 | | c-21=-4 | | 30-6x=3x+19 | | 5(7a-8)= | | 12-7x=35-14x | | 73*x=146 | | 4x^2+8x=252 | | x^2+8=10 | | 21m+84=0 | | 7m+28=0 | | 3m-6=48 | | 3m+6=0 | | -14=y-12 | | 5Y-25X=10 | | 5(4z-1)-3(z+7)=14(z+1) | | 7x+5y=4 | | 12x^2+63x+15=0 | | 0.5x^2+5=14 | | Y^2+10y-56=0 | | 4x^2-9=17 | | 4xy+24x-2x= | | x^2+3-5=0 | | 8x+17=2x+101 | | 6x^2+15=23 | | C^2+15=0 | | 70-4x=32x+22 | | x^2-3x+3=-3 | | 5z=3(z+7) | | 2[3x+5]=170 |

Equations solver categories